Deciphering Love: Two Close Readings of Philippine Lyrical Poetry from English - Galan, Ralph Semino (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
"Deciphering Love ’’ is part of an ongoing book project tentatively titled Elucidations: Close Readings in Philippine Poetry from English by author Galan. The said book will be a series of analyses of the works of 24 leading Filipino wordsmiths (12 male and 12 female) who write in English. The aim of the project is to make more accessible to the general public the verses of the selected authors. The chosen poems cover a variety of themes and subjects! love, family relationships, war and other atrocities, etc. Cesar Ruiz Aquino’s "Word Without End" and Edith L. Tempo’s "Bonsai" are two of the love poems that the author has opted to interpret, not only because of their moaning und meaningfulness, but also because of their linguistic density and suppleness.